Aerobic and anaerobic degradation of a range of alkyl sulfides by a denitrifying marine bacterium. - Visscher, P T (1993)
A pure culture of a bacterium was obtained from a marine microbial mat by using an anoxic medium containing dimethyl sulfide (DMS) and nitrate. The isolate grew aerobically or anaerobically as a denitrifier on alkyl sulfides, including DMS, dimethyl disulfide, diethyl sulfide (DES), ethyl methyl sulfide, dipropyl sulfide, dibutyl sulfide, and dibutyl disulfide. Cells grown on an alkyl sulfide or disulfide also oxidized the corresponding thiols, namely, methanethiol, ethanethiol, propanethiol, or butanethiol. Alkyl sulfides were metabolized by induced or derepressed cells with oxygen, nitrate, or nitrite as electron acceptor. Cells grown on DMS immediately metabolized DMS, but there was a lag before DES was consumed; with DES-grown cells, DES was immediately used but DMS was used only after a lag. Chloramphenicol prevented the eventual use of DES by DMS-grown cells and DMS use by DES-grown cells, respectively, indicating separate enzymes for the metabolism of methyl and ethyl groups. Growth was rapid on formate, acetate, propionate, and butyrate but slow on methanol. The organism also grew chemolithotrophically on thiosulfate with a decrease in pH; growth required carbonate in the medium. Growth on sulfide was also carbonate dependent but slow. The isolate was identified as a Thiobacillus sp. and designated strain ASN-1. It may have utility for removing alkyl sulfides, and also nitrate, nitrite, and sulfide, from wastewaters.